A influência do flúor na água nas condições de saúde bucal em escolares do município de Arealva - Paleari, Giovana Camila (2010)
In the field of buccal collective health lots have been searched in the aspects of tooth decay prevention. It means a infectum contagious degenerative multifatorial illness that destroys the teeth where its main etiological gent is the Streptococcus Bactirium from mutans group. This is considered a desease that attacks the Brazilian population in great number. According to several authors, water fluoridation from public supply is efficient and very important in tooth decay prevention and reaching the entire population where it covers. Therefore, the aim of this study was to evaluate the buccal health conditions in agreement to CPDO index (Lost and Filled theeth) and ceo (decidous extract, decayed and filled teeth) among children whether or not using fluoridated water. There were participating in the survey a total of 120 children in the age froup of 05 to 11 years old being them 60 children from Jacuba neighborhood (filled with water fluoridation) and 60 others from Santa Isabel neighborhood (not filled with fluoridation water). The results had shown that for ceo the rates ere significantly lower (P<0,05) in 7, 8 and upper 10 years old children. For CPDO rate the differences were statistically inferior (P<0,05) in 6, 7 and 8 year-old children from neighborhood where there s water fluoridation) In conclusion, it s noticed that water fluoridation is a way to minimize the ceo and CPDO rates in school age children.